2015
DOI: 10.3390/su7033001
|View full text |Cite
|
Sign up to set email alerts
|

Green and Blue Water Footprint Accounting for Dry Beans (Phaseolus vulgaris) in Primary Region of Mexico

Abstract: Abstract:Water shortages are a key obstacle to the sustainable supply of food to the world population, since agriculture has the largest consumptive water use. The Water Footprint (WF) has been developed as a useful tool to assess the contribution of goods and activities to water scarcity. This concept is being used around the world to improve agricultural water management. This paper analyzes climate data in order to estimate green and blue WFs for dry beans in the dry beans primary region of Mexico under bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…WFs can be reduced by diminishing the no beneficial component of evapotranspiration from crop fields, by mulching and better irrigation practices [25]. Adjustments in crop planting dates and selecting appropriate crop varieties that yield more crop per drop are other possible ways to increase water productivity and reduce WFs per tonne of crop [26,27]. In addition, knowledge on the water requirements per unit of crop under certain climatic conditions may result in a reconsideration of the crop production pattern in the country.…”
Section: Added Value Of Wf Assessment For Iran's Food and Water Securmentioning
confidence: 99%
“…WFs can be reduced by diminishing the no beneficial component of evapotranspiration from crop fields, by mulching and better irrigation practices [25]. Adjustments in crop planting dates and selecting appropriate crop varieties that yield more crop per drop are other possible ways to increase water productivity and reduce WFs per tonne of crop [26,27]. In addition, knowledge on the water requirements per unit of crop under certain climatic conditions may result in a reconsideration of the crop production pattern in the country.…”
Section: Added Value Of Wf Assessment For Iran's Food and Water Securmentioning
confidence: 99%
“…This study’s results demonstrated that an integrated approach based on inter-provincial trade network and structural modifications in the agricultural system would assure food self-sufficiency and control the water crisis. Cropping pattern modifications and associated increased water productivity and decreasing WF blue per ton of crops would be effective in controlling water crisis, something that has been reported previously in studies involving other regions [see, e.g., Lopez and Bautista-Capetillo 64 and Zhuo et al 65 ]. In fact, the weakness of Iranian policy is separating the trade network, food self-sufficiency, and water crisis.…”
Section: Resultsmentioning
confidence: 54%
“…The WF is an indicator that allows to evaluate the natural, economic and social sustainability of the water resource in a specific geographical area, and therefore, they play a fundamental role in the prevention and resolution of socio-environmental conflicts, associated with the use of the water resource (63,64) . Delgado (65) suggests that the inclusion of this indicator, as a water management strategy, allows communities to associate the relevance of efficient use of water resources in their territories, which is why WF is being used worldwide to improve water management in the different anthropic activities, which require the resource (66,67) . In addition, WF has been used in food safety studies as shown in Hong Kong where water use was evaluated according to the diets of the population with the purpose of determine critical or unsustainable diets, also, this study allowed to identify a decrease in per capita consumption of 355 to 326 l/day in two years by responsible consumption policies in this country (68) .…”
Section: Water Footprint and Its Relationship With Societymentioning
confidence: 99%